Genome-Wide Identification and Classification of MicroRNAs Derived from Repetitive Elements - Jeong-An Gim; Hong-Seok Ha; Kung Ahn; Dae-Soo Kim; Heui-Soo Kim (Genomics & Informatics)
MicroRNAs (miRNAs) are known for their role in mRNA silencing via interference pathways. Repetitive elements (REs) share several characteristics with endogenous precursor miRNAs. In this study, 406 previously identified and 1,494 novel RE-derived miRNAs were sorted from the GENCODE v.19 database using the RepeatMasker program. They were divided into six major types, based on their genomic structure. More novel RE-derived miRNAs were confirmed than identified as RE-derived miRNAs. In conclusion, many miRNAs have not yet been identified, most of which are derived from REs.